RFID Based Medical Database System - Mohamed Aminuddin, Mai Mariam; Misran, Mohamad Harris; Meor Said, Maizatul Alice; Salleh, Azahari; Othman, Mohd Azlishah; Ismail, Mohd Muzafar; Sulaiman, Hamzah Asyrani; Yusop, Norbayah; Ramlee, Ridza Azri (AENSI, 2013)
This paper present the medical database system which developed by using Radio Frequency Identification (RFID) system.The purpose is to improve and replace the traditional way of healthcare services which still using paper-data-recording system.This project also to facilitate the centralisation of patient records within the hospital environment.It is developed with the RFID system and web-based database of patient information.The project system functioning with data stored in the ID of patient card and the information web-based database will be administrating with Graphical User Interface (GUI). Overall this system requires RFID tag which is the patient ID card, RFID reader and computer in order to control the system work correctly.